AWARENESS ON THE INTERNAL STRUCTURE OF MORPHOLOGICALLY-COMPLEX WORDS AND ITS RELATIONSHIP TO VOCABULARY SIZE - Chothibul Umam (Celt: A Journal of Culture, English Language Teaching & Literature, 2015)
The present study examines the relationship between the students' awareness on the internal structure of morphologically-complex words (henceforth MCWs) and English vocabulary size of Indonesian EFL learners. The participants are 111 Indonesian EFL learners who had taken English Morphology subject. Two types of tests are used; Morpheme Identification Test was used to measure the students' awareness on the internal structure of MCWs and the vocabulary size test is used to estimate their vocabulary size. To know the relationship between the two variables, correlational analysis with Kendall-tau formula is then applied. The result shows that both variables have a positive and significant reciprocal correlation.